The Primary Management of Meningiomas - Elfigih, Ahmed Omar B. (faculty of Basic Medical Science - Libyan International Medical University, 2018)
Meningiomas are the most common primary brain tumors in adults and are therefore relevant for general practitioners. Most of them are benign, but atypical and anaplastic require multimodal treatment strategies including postoperative radiotherapy. These high grade tumors depend mainly on age and gender of the patient. Most studies support that radiation and surgery therapy reduces recurrence risk and improves overall survival for patients with high-grade meningiomas
A meningioma is a tumor that arises from a layer of tissue (the meninges) that covers the brain and spine. Meningiomas grow on the surface of the brain (or spinal cord), and therefore push the brain away rather than growing from within it. Most are considered “benign” because they are slow-growing with low potential to spread. Meningioma tumors can become quite large. Diameters of 2 inches (5 cm.) are not uncommon. Meningiomas that grow quickly and exhibit cancer-like behavior are called atypical meningiomas or anaplastic meningiomas, and are fortunately rare. Meningiomas represent about 20 percent of all tumors originating in the head and 10 percent of tumors of the spine. About 6,500 people are diagnosed with meningiomas each year in the United States. This type of tumor occurs more frequently in people with a hereditary disorder called neurofibromatosis type 2 (NF-2).1 But, how do we manage this disease? In this report, we are going to establish the primary management of meningioma